(untitled) (Journal Of Educational and Psychological Researches, 2018)
The research aims to identify the meaning of drug addiction, which being one of the behavioral-deviation signs. It largely seems similar to alcohol-addiction. World health organization has defined drug addiction as a sporadic or chronic-state of intoxication emerges of recurrent-consumption of drugs that impact harmfully on individual and society. The second aim is to study the psychological and health implications on drugs’ users and thirdly to design a psychological-program for those who take drugs.